Fatigue Strength Analysis of Metro KapsulÃâÃâs Bogie Frame Structure Using Finite Element Method - WIHARYANA (NIM : 13113118), DEDE
Metro Kapsul is a train produced by PT.Teknik Rekayasa KeretaKapsul. The structural component in Metro Kapsul that most affected by dynamic load is bogie. One way to ensure that the bogie structure is safe when subjected to dynamic loads is to do a fatigue test. To support the need for fatigue testing, it is necessary to do a fatigue analysis. The goal of this final project is to evaluate the fatigue strength of the Metro Kapsul's bogie frame structure and to obtain suitable position for strain gauge to be placed during fatigue testing. Fatigue analysis of the model is performed by using finite element method with solid element model. The bogie frame structure is analyzed based on the load definition and loading case on the EN 13749: 2011 standard. The methodology of this final project consist of literature study, collecting information about the model and specification of Metro Kapsul, formulation of loading case, finite element modeling, finite element finite validation. So that the analysis related to fatigue strength of bogie frame structure and critical location can be performed. Based on the results of fatigue analysis, the bogie frame structure can withstand fatigue loading more than the minimum repetition as required by EN 13749: 2011 standard. The critical location obtained, lies in the connection of the lower plate around the structure which receive lateral load, with a minimum repetition value of 65,000 reps in the first stage, 19,000 reps in the second stage and 3,500 reps in the third stage. The estimated design life of the Metro Kapsul's bogie frame on the specified track is 17 years for the first stage, 5 years for the second stage and 0,9 years for the third stage.